Physiological Factors Linking Insecure Attachment to Psychopathology: A Systematic Review - Marta Tironi (MDPI AG, 2021)
Although many studies have documented associations between insecure attachment and psychopathology, attachment may not confer risk for psychopathology independently, but rather through its interaction with emotional, social, and biological factors. Understanding the variables through which attachment may lead to psychopathology is therefore important. Within this domain of research, the role of physiological factors is poorly investigated. What are the relevant domains and why, when, or for whom do they influence mental disorders relating to attachment? The current systematic review aims to answer these questions. Results reveal that physiological indices of emotional regulation play a role in explaining and/or determining the relationship between attachment and psychopathology. Specifically: (1) combined with insecure attachment, higher skin conductance level (SCL), lower cardiac slowing, and respiratory sinus arrhythmia modulation (RSA) contribute to different psychopathological indicators and behavioral/psychological dysfunctions, although the latter predicts a contradictory pattern of findings; (2) insecure-avoidant attachment is more consistently linked with stress and emotional dysregulation when combined with RSA, while anxious attachment confers risk of depressive symptoms when combined with SCL. We concluded our discussion of the results of seven studies by outlining a plan to move the field forward. We discuss the quality of the assessment, methodological limitations, and future directions, highlighting the need to extend the research to clinical samples.